Plant height profiling in western India using LiDAR data - Tripathi, P.; Behera, M. D. (Current science (Bangalore), 2013)
Plant height has always been a subject of research in forest and vegetation sciences. Space-borne LiDAR data of Geoscience Laser Altimeter System (GLAS) on the Ice, Cloud and land Elevation Satellite (ICESat) have opened up new possibilities to analyse vegetation height. Here, we have analysed the plant height panorama for various forest vegetation classes of western India and understood their profile in terms of topography, vegetation canopy density and presence of heterogeneous features within the LiDAR footprints. Of the total 14,230 LiDAR hits for western India falling in 32 forest vegetation classes, we eliminated extreme plant height ranges to retain 9553 (67.13%) data points for further analysis. Maximum number of data points was observed over temperate coniferous forest, pine forest and desert dune scrub with 2119, 936 and 1770 number of LiDAR hits respectively. The maximum and minimum plant height range varied between 70 and 2.2 m for temperate coniferous forest and alpine scrub. In general, we noticed inaccuracy in the plant height estimates from GLAS data points for higher slope and elevation. Overestimation in data points could be attributed to the presence of anthropogenic features, viz. buildings, settlement and towers; and underestimation could be attributed to bare ground, agricultural field and water body owing to class heterogeneity and positional inaccuracy. This study provides a profile of plant heights from western India that can be used for structural characterization studies utilized in climate and ecological assessments.